Critical roles of G(i/o) proteins and phospholipase C-δ1 in the activation of receptor-operated TRPC4 channels - Thakur, Dhananjay P. (Proc Natl Acad Sci U S A, 2016)
Transient Receptor Potential Canonical (TRPC) proteins form nonselective cation channels commonly known to be activated downstream from receptors that signal through phospholipase C (PLC). Although TRPC3/C6/C7 can be directly activated by diacylglycerols produced by PLC breakdown of phosphatidylinositol 4,5-bisphosphate (PIP(2)), the mechanism by which the PLC pathway activates TRPC4/C5 remains unclear. We show here that TRPC4 activation requires coincident stimulation of G(i/o) subgroup of G proteins and PLCδ, with a preference for PLCδ1 over PLCδ3, but not necessarily the PLCβ pathway commonly thought to be involved in receptor-operated TRPC activation. In HEK293 cells coexpressing TRPC4 and G(i/o)-coupled µ opioid receptor, µ agonist elicited currents biphasically, with an initial slow phase preceding a rapidly developing phase. The currents were dependent on intracellular Ca(2+) and PIP(2). Reducing PIP(2) through phosphatases abolished the biphasic kinetics and increased the probability of channel activation by weak G(i/o) stimulation. In both HEK293 cells heterologously expressing TRPC4 and renal carcinoma-derived A-498 cells endogenously expressing TRPC4, channel activation was inhibited by knocking down PLCδ1 levels and almost completely eliminated by a dominant-negative PLCδ1 mutant and a constitutively active RhoA mutant. Conversely, the slow phase of G(i/o)-mediated TRPC4 activation was diminished by inhibiting RhoA or enhancing PLCδ function. Our data reveal an integrative mechanism of TRPC4 on detection of coincident G(i/o), Ca(2+), and PLC signaling, which is further modulated by the small GTPase RhoA. This mechanism is not shared with the closely related TRPC5, implicating unique roles of TRPC4 in signal integration in brain and other systems.